Phase Transitions Drive the Formation of Vesicular Stomatitis Virus Replication Compartments - Bianca S. Heinrich (American Society for Microbiology, 2018)
ABSTRACT RNA viruses that replicate in the cell cytoplasm typically concentrate their replication machinery within specialized compartments. This concentration favors enzymatic reactions and shields viral RNA from detection by cytosolic pattern recognition receptors. Nonsegmented negative-strand (NNS) RNA viruses, which include some of the most significant human, animal, and plant pathogens extant, form inclusions that are sites of RNA synthesis and are not circumscribed by a membrane. These inclusions share similarities with cellular protein/RNA structures such as P granules and nucleoli, which are phase-separated liquid compartments. Here we show that replication compartments of vesicular stomatitis virus (VSV) have the properties of liquid-like compartments that form by phase separation. Expression of the individual viral components of the replication machinery in cells demonstrates that the 3 viral proteins required for replication are sufficient to drive cytoplasmic phase separation. Therefore, liquid-liquid phase separation, previously linked to organization of P granules, nucleolus homeostasis, and cell signaling, plays a key role in host-pathogen interactions. This work suggests novel therapeutic approaches to the problem of combating NNS RNA viral infections. IMPORTANCE RNA viruses compartmentalize their replication machinery to evade detection by host pattern recognition receptors and concentrate the machinery of RNA synthesis. For positive-strand RNA viruses, RNA replication occurs in a virus-induced membrane-associated replication organelle. For NNS RNA viruses, the replication compartment is a cytoplasmic inclusion that is not circumscribed by a cellular membrane. Such structures were first observed in the cell bodies of neurons from humans infected with rabies virus and were termed Negri bodies. How the replication machinery that forms this inclusion remains associated in the absence of a membrane has been an enduring mystery. In this article, we present evidence that the VSV replication compartments form through phase separation. Phase separation is increasingly recognized as responsible for cellular structures as diverse as processing bodies (P-bodies) and nucleoli and was recently demonstrated for rabies virus. This article further links the fields of host-pathogen interaction with that of phase separation.